EFEKTIVITAS BUKU SISWA IPA TERPADU DENGAN TEMA ENERGI DALAM KEHIDUPAN BERBASIS MATERI LOKAL MENGGUNAKAN MODEL INTEGRATED UNTUK MENINGKATKAN KECAKAPAN ABAD 21 - Hidayat, Zaitul; Sarmi, Rahima Syabrina; Ratnawulan, Ratnawulan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
The current science student book is expected to have learning and assessment in it that is relevant to the demands of education now that is in accordance with 21stcentury learning that contains is critical and problem solving skills, creativity and innovation skills, collaboration skills, and communication skills it aims to develop the potential, talents and interests of students to have competent student who are ready to face global challenges. This article aims to evaluate the science student book with the theme of energy in life based integrated local materials using integrated models 21st century learning. Evaluation consists of testing the effectiveness of 21st century learning student?s skill after using this science student book. Thus, the results of study indicate that science student book with the theme of energy in life based integrated local materials using integrated models 21st century learning which is effectively used in student learning in class. Based on these result, it appears that science student book with the theme of energy in life based integrated local materials using integrated models can improve student?s High Order Thinking Skill (HOTS)